Thank you for the opportunity to help you with your question!

You have snapped it upside down and therefore am unable to see it well. However I will show you how to do this:

I guess this is the question

Given f(x)=2x^{2}-1 find

F((2+h)- f(2))/h

Solve for F(2+h) first

It becomes'

F(2+h)= 2(2+h)^{2} -1

Solve (2+h) (2+h)

4+2h +2h +h^{2}

Multiply it by 2 and adding gives

8+8h +2h^{2}

Subtract 1

=h^2+8h +7

Solve for F(2)

Remember we replace every occurrence of x with with the given value

It is 2(2)^{2}-1

=2(4)-1

=8-7

=7

Finish and solve

(F(2+h)- f(2))/h

F(2+h)= h^{2}+8h +7

f(2)= 7

Plugging them into the equation gives:

(h^{2} +8h +7 -7)/h

(h^{2} +8h)/h

Factorize the upper part

=h(h+8)

Dividing it by h leaves us with

h(h+8)/h

=h +8

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up